Unconditional : the Japanese surrender in World War II - Gallicchio, Marc, 1954- 1954- (Pivotal moments in American history, 2020)
Publishing on 75th anniversary of the Japanese surrender in September 1945, 'Unconditional' not only offers a narrative of the Japanese surrender in its historical moment, but reveals how the policy underlying it poisoned American postwar politics and warped our understanding of World War II for decades